Antibacterial and Cytotoxic Evaluation of Lespedeza cuneata Extract Against Periodontal Pathogens and Human Gingival Cells: A Novel Option for Periodontal Therapy - Hyo-Ju Yoon; Gyoo-Cheon Kim; Seoul-Hee Nam (Applied Sciences)
Background: This study aims to evaluate the antibacterial effect of Lespedeza cuneata extract on Porphyromonas gingivalis (P. gingivalis), a principal bacterium in periodontal disease, and its impact on human gingival fibroblasts (HGFs). Methods: Dried Lespedeza cuneata was extracted using 70% ethanol, concentrated, and freeze-dried to obtain the Lespedeza cuneata extract in powder form. The antibacterial effect, indicated by the inhibition of P. gingivalis growth, was assessed by administering concentrations of 1, 3, 5, 10, 20, 30, and 40 mg/mL. After 24 h of anaerobic incubation, colony-forming units per milliliter (CFU/mL) were measured. Cytotoxicity on HGF cells was evaluated after treatment with WST-1 solution followed by incubation at 37 °C, 5% CO2 for 2 h. Cell morphology and proliferation were assessed using the Sulforhodamine B (SRB) assay. Results: The antibacterial effect of Lespedeza cuneata extract was concentration-dependent, with 99.98% inhibition observed at 5 mg/mL, 99.99% at 10 mg/mL, and no detectable CFUs were observed at 40 mg/mL under the tested conditions. Evaluating the change in growth rate of HGF cells showed a decrease in cell viability as the concentration increased, and the application of Lespedeza cuneata extract at 10 mg/mL was found to be a safe and effective concentration with a half-maximal inhibitory concentration (IC50). Conclusion: Based on the antibacterial effect, cytotoxicity, and safety profile of Lespedeza cuneata extract, it holds potential as a natural extract material for the prevention, improvement, or treatment of periodontal disease. Additionally, validation of the practical approach will be necessary via a clinical applicability evaluation.